DEVELOPMENT APPROACHES AND STRATEGIC MOVEMENTS WITHIN THE MOBILE TELECOMMUNICATION FIELD - Gheorghe MEGHISAN; Georgeta-Madalina MEGHISAN (Management & Marketing)
In February 2000, when Vodafone took control of the British operatorOrange, they had to split, because Vodafone owned two mobile telephonylicenses in the same country – Great Britain – fact that was interdicted by theEuropean legislation. So, on 30th of May 2000, France Telecom announcedthe purchase of the mobile telephony operator – Orange public limitedcompany (plc) – from Vodafone for the amount of 40 billion euro.Focusing on the fusion – acquisition as a way of development for the mobiletelecommunication companies, this paper begins with a theoretical analyze ofsome concepts related to the external growth. The example taken reveals theadvantages and disadvantages of the fusion – acquisition France Telecom –Orange as well as the dangers that an enterprise has to face when it decidesto appeal to the external growth.